2016
DOI: 10.1177/1087054715623045
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficits in Adult ADHD: Evidence for Differential Attentional Impairments, Deficient Executive Functions, and High Self-Reported Functional Impairments

Abstract: This pattern of results suggests differential impairments of attentional skills. Impaired executive functions and higher subjective functional impairments were also found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…Overall, the results of the case assessments showed impairments in cognitive functioning domains mainly related to attention, executive function (inhibitory control and phonemic fluency), and memory, and a predominance of slow reaction times in CPT. Although these cognitive findings do not characterize ADHD by themselves, they are consistent with previous literature (Hervey et al, 2004; Seidman, 2006; Kofler et al, 2013; Faraone et al, 2015; Mostert et al, 2015; Salomone et al, 2016; Weyandt et al, 2017), except for both participants’ performance in the working memory domain, which was average. This inconsistency with the literature may reflect possible variations (individual differences) that are found within a larger sample since ADHD in older adults was recently found to be associated with lower cognitive functioning in working memory (Semeijn et al, 2015; Thorell et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the results of the case assessments showed impairments in cognitive functioning domains mainly related to attention, executive function (inhibitory control and phonemic fluency), and memory, and a predominance of slow reaction times in CPT. Although these cognitive findings do not characterize ADHD by themselves, they are consistent with previous literature (Hervey et al, 2004; Seidman, 2006; Kofler et al, 2013; Faraone et al, 2015; Mostert et al, 2015; Salomone et al, 2016; Weyandt et al, 2017), except for both participants’ performance in the working memory domain, which was average. This inconsistency with the literature may reflect possible variations (individual differences) that are found within a larger sample since ADHD in older adults was recently found to be associated with lower cognitive functioning in working memory (Semeijn et al, 2015; Thorell et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Although studies show an age-dependent decline in ADHD symptoms (Michielsen et al, 2012; Das et al, 2014), the persistence of symptoms might also lead to significant impairment in older age with a cumulative impact (Kooij et al, 2016; Srinivasan et al, 2016). Moreover, multiple domains of neurocognitive impairment such as executive function, attention, memory, and language are common in children (Sjöwall et al, 2013, 2015; Martino et al, 2017; Salari et al, 2017; Fabio et al, 2018; Shephard et al, 2018; Sjöwall and Thorell, 2019), adolescents (Fried et al, 2016; Steward et al, 2017; Weyandt et al, 2017), and young adults with ADHD (Faraone et al, 2015; Mostert et al, 2015; Antshel et al, 2016; Salomone et al, 2016). Recent studies suggest that some of these impairments may persist in older adults (Fuermaier et al, 2013; Thorell et al, 2017; Coelho et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We also recognize that we used very broadly defined neuropsychological domains to capture the heterogeneous, comprehensive performance of ADHD. Previous research has suggested more specific performance characteristics in ADHD, for example, verbal long-term memory (Schoechlin & Engel, 2005), memory acquisition processes (Skodzik et al, 2017), and divided and sustained attention (Salomone, Fleming, Bramham, O’Connell, & Robertson, 2016). Therefore, our results may be indicative of the domains we chose and different results could have been obtained by evaluating subdomains.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies show that many psychological disorders and illnesses, such as spina bifida, cerebral palsy, schizophrenia, dyslexia, attention deficit with hyperactivity disorder, autism spectrum disorder, as well as others, are accompanied by deficits in EF, which hinder their adaptation to the environment anales de psicología / annals of psychology, 2020, vol. 36, nº 1 (january) (Iampietro, Giovannetti, Drabick, & Kessler, 2012;Moura, Simões, & Pereira, 2015;Piovesana, Ross, Whittingham, Ware, & Boyd, 2015;Salomone, Fleming, Bramham, O'Connell, & Robertson, 2016;Zabel et al, 2011).. In addition, deficits in EF are observed in some populations with social difficulties, such as children from disadvantaged families (Devicienti & Poggi, 2011;Dickerson & Popli, 2016).…”
Section: Introductionmentioning
confidence: 99%